Pemanfaatan Galon Bekas Air Mineral Sebagai Tempat Media Tanam Untuk Mendukung Program Go Green - Nur Solikah, Umi; Mulyadi; Kisnowo; Pranoto, Panggih; Setyawan, Bambang (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Information technology has developed and provided progress such as the increasing use of computers and the internet in the world, especially in the world of education. Through computers and the internet, all information can be disseminated and can be used as learning materials for students. The development of information technology and the internet, not all information is disseminated positively. Some information is disseminated negatively such as fake news (hoaxes), radicalism, and hate speech. There needs to be skills in using the development of information technology. Digital literacy trains users not only to be proficient in using information technology but also to have the ability to think critically, creatively, and innovatively to produce digital competence. SMA At Thohiriyyah is one of the high schools in Semarang that focuses on understanding and improving the abilities of its students in digital literacy. Insight is needed for SMA At Thohiriyyah students in understanding the importance of digital literacy. Animation video training is one way to increase student creativity in digital literacy in creating learning videos. With this training, it is hoped that students can develop learning videos that can be used on social media such as YouTube